MENGGUNAKAN MEDIA INTERNET DOCS.GOOGLE PADA POKOK BAHASAN REAKSI REDOKS KELAS X IPA DI SMAN 4 KOTA BENGKULU - Aang Parade; Dewi Handayani; Sumpono Sumpono (ALOTROP, 2018)
[USING THE DOCS. GOOGLE INTERNET MEDIA ON THE REDOX REACTION  SUBJECT IN CLASS X IPA SMAN 4 BENGKULU CITY  ] This research aims to know the results of learning: students in the class who are not given the preparation of learning at home, knowing the results of the teaching of students in a given grade of preparatory study at home using internet media, knowing the Docs. Google the difference in the results of student learning in the classroom are not given preparation home study with the results of a survey of students in a provided a homework preparatory sign Docs. Google internet media. The methods used in this research was quasi-experimental research is the entire population with grade X IPA SMAN 4 city of Bengkulu, Sample research, i.e., class experiments and classroom control. The results of the study in this research result of students pretest and posttest. Based on the results of the research conducted in mind that there is a significant difference between the results from student learning in the classroom are not given preparation home study with the results of a survey of students in a given a homework preparation home study using internet media Docs. Google via t-tests using SPSS 16 program. The learning outcomes of students in a given grade of preparatory education at home using Google Docs. Indicates the average rating of 77.0 while learning results of students in the class who are not given a homework preliminary with the average value of 68.6. Student Learning Outcomes in a given class homework preparation using Docs. Google may provide better results on the subject of redox reactions.